2021
DOI: 10.23887/jere.v5i2.30386
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of English Teachers’ Authentic Assessment in Junior High School During Online Learning

Abstract: Authentic assessment is assessment to define students’ reflection of their learning, achievement, motivation, and attitudes during the learning instruction. Implementing authentic assessment reflects real-world situation and allow students to solve problem with possible solutions. This research aimed at investigating the English teachers’ authentic assessment implementation during online learning. This research was descriptive qualitative research. The research subject was three English Teachers in SMP Negeri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…In order to find the result, Daud et al (2020) utilize an activity named a seminar. The finding also different from Putri et al, (2021). They found three issues in teaching-learning process faced by the teachers, there are time limitation, amount of students, and the materials.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In order to find the result, Daud et al (2020) utilize an activity named a seminar. The finding also different from Putri et al, (2021). They found three issues in teaching-learning process faced by the teachers, there are time limitation, amount of students, and the materials.…”
Section: Discussionmentioning
confidence: 78%
“…In line with this research finding, Daud et al, (2020) also found that an appropriate way of teaching speaking can improve students' speaking ability. Besides, Putri et al, (2021) described the application of authentic assessment done by English teachers in online learning. Unfortunately, they found that the teachers did not apply all types of authentic assessment as planned before due to time limitation, the number of students in a class, and the materials.…”
Section: Introductionmentioning
confidence: 99%